Child abuse and parental Burnout in COVID-19 pandemic: a review (Research, Society and Development, 2022)
This is an integrative review that discusses how parental Burnout in the context of the COVID-19 pandemic may be related to child abuse. The search was carried out in the PubMed, SciELO, Web of Science, PsycINFO, CINAHL, LILACS and Google Scholar databases, using the descriptors "child violence", "psychological exhaustion", "COVID-19", “Health teaching” and related terms, together with the operators Booleans. The eleven selected articles deal with topics such as: families in the COVID-19 pandemic; impacts of COVID-19 and child abuse and social isolation from parents and; risk of child abuse during the COVID-19 pandemic. During the pandemic, parental stress, which is the main cause of Burnout, increased significantly due to unemployment, financial insecurity, low levels of social support, closing schools, decreasing leisure, increasing workload and responsibilities towards the family, which can lead to consequences such as child violence.